1996
DOI: 10.1016/1071-5576(95)00036-4
|View full text |Cite
|
Sign up to set email alerts
|

Serum interleukin-2 and soluble interleukin-2 receptor in gestational trophoblastic diseases

Abstract: The possible causes of IL-2 decreases and SIL-2R increases may indicate a defective immune response in GTDs. The high correlation between SIL-2R level and tumor burden suggests the use of serum SIL-2R assay for disease monitoring: SIL-2R is indirect marker of tumor activity, and it is useful in the differential diagnosis of GTD because a normal value of serum SIL-2R excludes high-risk cases of choriocarcinoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2006
2006
2009
2009

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…It might be due to sIL-2R could combine with IL-2 and then hinder IL-2 to interact with IL-2R expressed on lymphocytes. Shaarawy et al (95) found the concentration of descendence in IL-2 and asendence in sIL-2R in sera of patients with molar pregnancy and choriocarcinoma, especially in all high-risk choriocarcinoma cases, extremely high sIL-2R was found. This findings suggested that cellular immune reactivity was suppressed in patients with GTD patients and sIL-2 may be one of biomarkers for high-risk choriocarcinoma.…”
Section: Suppressive Cytokinesmentioning
confidence: 97%
“…It might be due to sIL-2R could combine with IL-2 and then hinder IL-2 to interact with IL-2R expressed on lymphocytes. Shaarawy et al (95) found the concentration of descendence in IL-2 and asendence in sIL-2R in sera of patients with molar pregnancy and choriocarcinoma, especially in all high-risk choriocarcinoma cases, extremely high sIL-2R was found. This findings suggested that cellular immune reactivity was suppressed in patients with GTD patients and sIL-2 may be one of biomarkers for high-risk choriocarcinoma.…”
Section: Suppressive Cytokinesmentioning
confidence: 97%